The family Opilioacaridae (Parasitiformes: Opilioacarida) in Mexico, description of two new species, new records, and geographical distribution - Vázquez, Ma. Magdalena; Castaño-Meneses, Gabriela; Rodríguez, Abraham (Zootaxa, 2022)
Two new species of Neocarus (Opilioacarida: Opilioacaridae), N. haicolous n. sp. and N. queretanus n. sp., are described from mesophyll and pine-oak forests in the state of Querétaro, central Mexico. One species was described from adults and tritonymphs. Distribution and habitat preferences of all known collections of Opilioacarida are reviewed. In Mexico, they have been collected in all habitats, from semideserts areas to tropical forest and from to sea level in dunes to high temperate and cloud forest.